Disorder enabled band structure engineering of a topological insulator surface - Yishuai Xu (Nature Portfolio, 2017)
The surface electrons in a topological insulator are resistant to localization by nonmagnetic disorder, but are affected by lattice disorder. Here, the authors show that resonance states near lattice defects on the surface have significance beyond the localized regime usually associated with impurity bands.